Organic Fertilization in ’Pérola’ Pineapple Increases Fruit Production and Physical and Chemical Characteristics - Irineu, Toni Halan Silva; Mendonça, Vander; Moura, Elias Ariel; Lima, Franciezer Vicente; Oliveira, Luana Mendes; Melo, Marlenildo Ferreira; Mendonça , Luciana Freitas Medeiros; Chagas, Pollyana Cardoso (Comunicata Scientiae, 2023)
Pineapple is the third most cultivated tropical fruit in the world. However, few studies have focused on the cultivation using organic fertilization, especially in semiarid regions. Thus, this study aimed to evaluate growth, production and physicochemical traits of pineapple fruits produced under organic fertilization in the semiarid. The experiment was carried out at the didactic orchard of Federal Rural University of Semiarid, Mossoró, Rio Grande do Norte, Brazil. Four fertilization treatments were studied (chemical fertilizer, cattle manure, goat manure, poultry litter). At 18 months after planting, plant growth, physicochemical traits of fruits, and productivity were evaluated. Results showed that organic fertilization with poultry litter provides best results for physicochemical traits of fruits and productivity of ‘Pérola’ pineapple. Organic fertilization with poultry litter is most promising for plant growth, physicochemical traits of fruits, and productivity in ‘Pérola’ pineapple, therefore, the most suitable for cultivation in the semiarid region. The fruit firmness, central cylinder weight, and ratio SS/TA showed best values under chemical and goat manure fertilization.